Dampak Bauran Pemasaran Terhadap Kepuasan Konsumen Serta Pengaruh Loyalitas Pelanggan Pada Produk Samsung Di Kendari - Muhamad Pariama; . Kusrawan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2018)
One of the marketing element that affect consumer behavior is the combinationof product management and promotion mix. Samsung is one big company that hasmany users and they are very loyal. But due to lack of innovation, then theloyalty of its users were also reduced. Kendari as one of the regionalmarkets in Indonesia surprisingly placed Xiaomi was in first rank in mobilephone brand loyalty for the first time. This is quite surprising considering Samsung is able to defeat the famous Apple that has a strong user base, loyal,and fanatical, but in fact, Samsung has a bigger share of the market. Thepopulation used in this study is the people who use Samsung products in Kendari City. This study the number of samples used is 120 people . Hypothesistesting was done by using indicators CR and P. Because of the 9 hypothesistested in this study have CR value above 1.96 or P value smaller than 0.05,Then all hypotheses tested reject Ho and accept H1. In other words theindependence and intervening variables have the effect of increasing thedependent variable if only the independent variables and the intervening canbe improved by Samsung product manufacturers.